A captivating journey of memory and healing: A review of a novel book “Sebuah usaha melupakan” by Boy Chandra (2016) - Wajdi, Majid; Setiadewi, Ni Putu Chesya Putri; Ratih, Ni Kadek Pande Ayu; Dewi, Ni Ketut Citra; Suteja, Mutira Kristiani; Pridari, Ni Made Mira (Journal of Language and Pragmatics Studies, 2023)
This study tries to review an Indonesian novel "Sebuah Usaha Untuk Melupakan" (2016). This novel is a thought-provoking novel by Boy Chardra that delves into the intricate web of human emotions, memories, and the powerful journey of healing. Set against the   backdrop of a bustling city, the story follows the  protagonist as he embarks on a quest to forget a haunting past and find solace in the present. As the novel unfolds, the protagonist encounters a diverse cast of characters who contribute to his transformative journey. Each interaction serves as a catalyst for self-reflection, challenging his perceptions and forcing him to confront the painful memories that haunt him. The narrative weaves seamlessly between past and present, gradually unraveling the layers of    the protagonist's history and offering glimpses of  hope and redemption. The writer's evocative prose paints a vivid picture of the urban landscape, mirroring the protagonist's internal struggles. The city becomes a metaphorical canvas upon which the protagonist attempts to forge a new identity and escape the clutches of his past. Through atmospheric descriptions and poetic imagery, the author creates a palpable sense of time and place, immersing readers in the protagonist's world. The novel explores universal themes of love, loss, and the intricate nature of memory. The writer skillfully crafts a narrative that not only captivates readers but also prompts them to reflect on their own experiences. The novel serves as a poignant reminder that healing and growth often require confronting one's past, embracing vulnerability, and on a transformative journey towards self-discovery. This novel is a compelling novel that navigates the complex terrain of memory and  healing with grace and sensitivity. The writer’s masterful storytelling and introspective exploration of the human condition make this book a memorable read, resonating with readers long after the final page is turned.